Stealth Station® Treon®Plus neuronavigation system in surgery of intracranial meningiomas - Sirko, A. G.; Zorin, N. A.; Novik, Yu. E.; Kirpa, I. Yu.; Shpohnka, V. I. (Ukrainian Neurosurgical Journal, 2010)
The initial experience of Stealth Station® Treon®Plus neuronavigation system using for intracranial meningiomas surgery have been analyzed. Neuronavigation was used to perform operations at 17 patients. The technology of system using was given in details. Neuronavigation is an effective tool for preoperative planning and intraoperative assistance in neurosurgical practice. Involving CT-angiography images into preoperative planning protocol provided additional accuracy in critical vessels identification. Neuronavigative system application in addition to standard technologies (surgical microscope, microsurgical techniques, ultrasound aspirator, and argon plasma coagulation) allowed to increase surgery radicalism and to achieving good functional outcomes.